Cross-sectional associations between effort-reward imbalance at work and oral diseases in Japan - Yukihiro Sato; Eiji Yoshioka; Masanori Takekawa; Yasuaki Saijo (PeerJ, 2022)
Background Psychological stress is a potential risk factor for oral diseases. However, evidence for the association between work stress and oral diseases is scarce. We aimed to examine the associations of work stress, according to the effort-reward imbalance model, with dental caries, periodontal status, and tooth loss. Methods This cross-sectional study included 184 regular employees at a medical university and 435 registrants of a web research company. Work stress was assessed using the effort-reward imbalance (ERI) ratio. Dental caries and tooth loss were assessed according to the number of decayed, filled, and missing teeth (DMFT) among the set of 28 teeth. Periodontal status was assessed using a self-administered questionnaire. For the DMFT, a linear regression model was used to estimate the unstandardised coefficients. A Poisson regression model was used to estimate the prevalence ratios (PRs) of poor periodontal status. Results Among medical university employees and employees enrolled from among the registrants of an online research company, a one-unit increase in the ERI ratio was associated with −2.81 (95% CI [−4.70 to −0.92]; p-value = 0.004) and −0.84 (95% CI [−1.80 to 0.12]; p-value = 0.085) changes in the DMFT from adjusted linear regression models, respectively. In employees enrolled from among the registrants of an online research company, a one-unit increase in the ERI ratio was also associated with 1.55 (95% CI [1.04–2.32]; p-value = 0.032) of the PR for poor periodontal status based on Poisson regression models. Conclusion ERI at work was associated with an increased risk of poor periodontal status.